Pengetahuan dan Sikap Remaja Putri Terhadap Dysmenorrhea di SMPN 008 Rambah Hilir Tahun 2013 - ,, Andria (Jurnal Martenity and Neonatal, 2013)
The incidence of dysmenorrhea in the world is quite high , an estimated 50 % of all women in the world suffer from dysmenorrhea in a menstrual cycle . Indonesia 90% of women had experienced dysmenorrhea . The purpose of this study was to determine the knowledge and attitudes of young women against dysmenorrhea in the SMP 008 Rambah Downstream Year 2013. This type of research is descriptive cross sectional approach . This research was conducted in June 2013. With a sample size of 30 respondents . Sampling was done by taking all members of the population being sampled , method of data collection using primary data obtained from questionnaires with Univariate analyzes were performed in adolescents in class VII and VIII Junior High School 008 on the Lower Rambah Year 2013. The results showed good knowledgeable respondents were 22 persons ( 73.3 % ) , knowledgeable enough for 6 people ( 20 % ) , and less berpengatahuan 2 ( 6.7 % ) and the attitude of the majority of the respondents in the face of positive dysmenorrhea 29 people ( 96.7 % ) and the minority being negative numbered 1 ( 3.3 % ) . Researchers of this study suggest that the mass media and electronic media are very important in education, especially on matters related to dysmenorrhea